Radiation Increases Bioavailability of Lisinopril, a Mitigator of Radiation-Induced Toxicities - Meetha Medhora; Meetha Medhora; Meetha Medhora; Meetha Medhora; Meetha Medhora; Preeya Phadnis; Jayashree Narayanan; Tracy Gasperetti; Jacek Zielonka; Jacek Zielonka; John E. Moulder; Brian L. Fish; et al. (Frontiers Media S.A., 2021)
There are no FDA-approved drugs to mitigate the delayed effects of radiation exposure that may occur after a radiological attack or nuclear accident. To date, angiotensin-converting enzyme inhibitors are one of the most successful candidates for mitigation of hematopoietic, lung, kidney, and brain injuries in rodent models and may mitigate delayed radiation injuries after radiotherapy. Rat models of partial body irradiation sparing part of one hind leg (leg-out PBI) have been developed to simultaneously expose multiple organs to high doses of ionizing radiation and avoid lethal hematological toxicity to study the late effects of radiation. Exposures between 9 and 14 Gy damage the gut and bone marrow (acute radiation syndrome), followed by delayed injuries to the lung, heart, and kidney. The goal of the current study is to compare the pharmacokinetics (PK) of a lead angiotensin converting enzyme (ACE) inhibitor, lisinopril, in irradiated vs. nonirradiated rats, as a step toward licensure by the FDA.Methods: Female WAG/RijCmcr rats were irradiated with 12.5-13 Gy leg-out PBI. At day 35 after irradiation, during a latent period for injury, irradiated and nonirradiated siblings received a single gavage (0.3 mg, 0.6 mg) or intravenous injection (0.06 mg) of lisinopril. Plasma, urine, lung, liver and kidney levels of lisinopril were measured at different times. PK modeling (R package) was performed to track distribution of lisinopril in different compartments.Results: A two-compartment (central plasma and periphery) PK model best fit lisinopril measurements, with two additional components, the gavage and urine. The absorption and renal clearance rates were similar between nonirradiated and irradiated animals (respectively: ratios 0.883, p = 0.527; 0.943, p = 0.605). Inter-compartmental clearance (from plasma to periphery) for the irradiated rats was lower than for the nonirradiated rats (ratio 0.615, p = 0.003), while the bioavailability of the drug was 33% higher (ratio = 1.326, p < 0.001).Interpretation: Since receptors for lisinopril are present in endothelial cells lining blood vessels, and radiation induces vascular regression, it is possible that less lisinopril remains bound in irradiated rats, increasing circulating levels of the drug. However, this study cannot rule out changes in total amount of lisinopril absorbed or excreted long-term, after irradiation in rats.